Factors associated with exclusive formula feeding among individuals with low‐risk pregnancies in the United States. Issue 1 (13th January 2023) - Fishel Bartal, Michal; Huntley, Erin S.; Chen, Han‐Yang; Huntley, Benjamin J. F.; Wagner, Stephen M.; Sibai, Baha M.; Chauhan, Suneet P.
Abstract: Background: Better understanding of the factors associated with formula feeding during the hospital stay can help in identifying potential lactation problems and promote early intervention. Our aim was to ascertain factors associated with exclusive formula feeding in newborns of low‐risk pregnancies. Methods: A population‐based, retrospective study using the United States vital statistics datasets (2014‐2018) evaluating low‐risk pregnancies with a nonanomalous singleton delivery from 37 to 41 weeks. People with hypertensive disorders, or diabetes, were excluded. Primary outcome was newborn feeding (breast vs exclusive formula feeding) during hospital stay. Adjusted relative risks (aRRs) with 95% confidence intervals (CI) were calculated. Results: Of the 19 623 195 live births during the study period, 11 605 242 (59.1%) met inclusion criteria and among them, 1 929 526 (16.6%) were formula fed. Factors associated with formula feeding included: age < 20 years (aRR 1.31 [95% CI 1.31‐1.32]), non‐Hispanic Black (1.42, 1.41‐1.42), high school education (1.69, 1.69‐1.70) or less than high school education (1.94, 1.93, 1.95), Medicaid insurance (1.52, 1.51, 1.52), body mass index (BMI) < 18.5 (1.10, 1.09‐1.10), BMI 25‐29.9 (1.09, 1.09‐1.09), BMI 30‐34.9 (1.19, 1.19‐1.20), BMI 35‐39.9 (1.31, 1.30‐1.31), BMI ≥ 40 (1.43, 1.42‐1.44), multiparity (1.29, 1.29‐1.30), lack of prenatal care (1.49, 1.48‐1.50), smoking (1.75, 1.74‐1.75), and gestational age (ranged from 37 weeks [1.44, 1.43‐1.45] to 40 weeks [1.11, 1.11‐1.12]). Conclusions: Using a large cohort of low‐risk pregnancies, we identified several modifiable factors associated with newborn feeding (eg, prepregnancy BMI, access to prenatal care, and smoking cessation). Improving the breast feeding initiation rate should be a priority in our current practice to ensure equitable care for all neonates.